Outcome of Occupational Asthma after Removal from Exposure: A Follow-Up Study - Catherine Lemiere; Simone Chaboillez; Mélanie Welman; Karim Maghni (Canadian Respiratory Journal)
BACKGROUND: Despite being removed from their workplace, the majority of workers with occupational asthma (OA) remain afflicted with asthma.